Academic Senate Minutes 2008-09-18 - Academic Senate:::::::::
Minutes of 9/4/08 approved. Announcement from the Chair. Agenda approved. Associated Students report. SAC report. FSAC report. SBC report. Special Visit: Mayor Jake Mackenzie of Rohnert Park. Chair-Elect report. Chair Report. Art Therapy Discontinuance approved. Provost Report. Good of the Order.